OrtoWeb: from contents as an IT based learning environment for Orthodox Religion Education - Aikonen, Risto (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2025)
In Finland the Orthodox Church is a minority religion. The members of the Orthodox Church make up 1% of the total Finnish population of about 5.5 million. The Finnish-speaking Orthodox Church is autonomous and belongs to the Ecumenical Patriarchate of Constantinople. Religion teaching is taught in public schools. It is a compulsory subject for the pupils at both at Elementary and Secondary Schools (Lower and Upper). Every school year there are throughout the country about 6000 pupils who are members of the Christian Orthodox Church and they are taught by 300 teachers. Of those 4/5 are part-time teachers (Primary School Teachers) of the religion lessons. Almost every second teacher is working as a full-time primary school teacher (Aikonen 1997). The members of the Orthodox Church are spread out all over Finland because of the Second World War, when about 400 000 Finns had to leave their homes in the area called Carelia and were resettled throughout the country. Most of these people were Orthodox Christians. Today the parishes are rather small and most Orthodox Christians live in the eastern and southern parts of the country. In spite of the good educational infrastructure, every year there are pupils who cannot be reached by religion lessons.